Absenteeism as a Mechanism for Approaching an Optimal Labor Market Equilibrium: An Empirical Study - Dunn, L. F.; Youngblood, Stuart A. (The Review of Economics and Statistics, 1986)
L. F. Dunn, Stuart A. Youngblood, Absenteeism as a Mechanism for Approaching an Optimal Labor Market Equilibrium: An Empirical Study, The Review of Economics and Statistics, Vol. 68, No. 4 (Nov., 1986), pp. 668-674